Myocardial energetic efficiency is depressed in ischemia with non-obstructive coronary arteries. (25th November 2020) - Eskerud, I; Mancusi, C; Khan, I; Berge, C.A; Larsen, T; Lonnebakken, M.T
Abstract: Background: Ischemia with non-obstructive coronary arteries (INOCA) is incompletely understood. Depressed myocardial energetic efficiency index (MEEi), the ratio between external work and myocardial oxygen consumption, has been shown in heart failure. However, MEEi in INOCA has not been explored. Purpose: To test whether MEEi is associated with INOCA. Methods: We included 125 patients (56% women, age 62±9 years) with exercise-induced chest pain and non-obstructive coronary arteries (stenosis <50%) by coronary computed tomography angiography (CCTA). Stroke volume (SV) and left ventricular (LV) mass were assessed by echocardiography. MEEi was calculated as (systolic blood pressure (SBP) x SV) / (SBP x heart rate) and normalized for LV mass. LV hypertrophy was defined as LV mass index >46.7 g/m 2.7 in women and >49.2 g/m 2.7 in men. Myocardial ischemia was detected by myocardial contrast stress echocardiography. Coronary artery plaque burden was measured as plaque volume by CCTA. Results: In univariable regression analysis, stress-induced ischemia, male sex, diabetes, hypertension, LV hypertrophy, lower LV ejection fraction and higher SBP were associated with MEEi (all p<0.05). There were no associations with age, obesity or coronary artery plaque burden. MEEi was lower in patients with stress-induced ischemia (n=66) compared to patients without ischemia (0.47±0.16 vs. 0.54±0.21 ml/sec x g –1, p=0.026). In multivariable linear regression analysis, MEEi remained associated with stress-induced myocardial ischemia after adjustment for cardiovascular risk factors, SBP, LV hypertrophy, LV ejection fraction and coronary artery plaque burden (R 2 0.26, p<0.001, Table). Conclusion: MEEi is depressed in patients with INOCA. Our results suggest that myocardial ischemia negatively influences MEEi in patients with non-obstructive coronary arteries. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Western Norway Regional Health Authority, University of Bergen